Build with intrinsic security: Trusted autonomy security system - Shen He; Jing Huang; Penglin Yang (International Journal of Distributed Sensor Networks)
Security of Internet of things network is difficult to manage because Internet of things devices are heterogeneous and always deployed in remote places. Based on these features, attacks against Internet of things network like distributed denial-of-service and system intrusion are easier than traditional network. In order to enhance Internet of things network’s security, in this article we propose the concept of intrinsic security to establish a trusted and autonomy Internet of things network. Intrinsic security emphasizes that network itself must be trusted and security autonomous to address the security problems which are caused by remote and heterogeneous. Based on this thought, we designed the architecture of Trusted Autonomy Security System. Trusted Autonomy Security System maintains a LAN characterized by trusted and security autonomy, in which all Internet of things network gateways formed a decentralized autonomy system to evaluate if other gateways or Internet of things devices are secure. Compared to traditional Internet of things networks, this architecture uses trusted computing technique to build the basic of security, and makes Internet of things network available to manage security automatically. In addition, the decentralized architecture could reduce security risks caused by compromise of single node in Internet of things network. With these advantages, it can be expected that this novel idea will have more development in Internet of things scenarios with high security requirements.